The Internalization of Character Education Values and the Concept of Happiness Through the Short Story "Al-Saeed Hasan" by Kamil Kailani: Children's Literature Study - Muhimmah, Sulukul; Zawawi, Moh (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. The surge in juvenile delinquency cases proves that character education plays an important role in shaping an individual’s personality. Character education values also contribute an individual’s understanding and creation of happiness. This research aims to (1) present the values of character education in the short story "Al-Saeed Hasan"; (2) describe the concept of happiness in the short story "Al-Saeed Hasan" by Kamil Kailani. The method used in this research was descriptive qualitative. The primary data source in this research was from a short story titled "Al-Saeed Hasan" by Kamil Kailani. Meanwhile, the secondary data sources were references from articles, journals, and other relevant literature to the discussion in this research. The data collection technique used the read and note method. Furthermore, the data were analyzed using the analysis model from Milles and Huberman by conducting data reduction, data presentation, and drawing conclusions. This research found (1) 21 instances of character education values, with 6 religious values, 2 honesty, 2 curiosity, 2 friendliness/communicativeness, 3 love of peace, and 6 responsibility. (2) The concept of happiness was found in 5 instances, with 2 involving knowledge of God and nature, and 3 involving moral actions and affection. Based on the results of the research above, it can be concluded that children's literature is not only used for entertainment but also as an educational tool, such as instilling the values of character education and the concept of happiness for children. Moreover, children's literature can also influence character formation and psychological development in children.Keywords: The Value Of Character Education, The Concept Of Happiness, Children's Literature